The association of coffee consumption rate with serum 25-hydroxyvitamin D, non-HDL levels, and TC/HDL ratio in females with vitamin D deficiency - Maha Habash; Sami Al-shakhshir; Mohammad Abusamak; Mohammad Yasin Mohammad; Mahmoud AbuSamak (Women's Health, 2022)
Objectives: The purpose of this study was to evaluate the association of coffee consumption rate with serum 25-hydroxyvitamin D, non-high-density lipoprotein cholesterol levels, and total cholesterol to high-density lipoprotein cholesterol ratio in females with vitamin D deficiency. Methods: This retrospective cross-sectional study was carried out by studying the records of 270 Jordanian females aged 18–65 years with varying degrees of vitamin D deficiency. Following completion of the questionnaire regarding their anthropometric characteristics and coffee consumption rate during the preceding 3 months, the participants were required to provide blood samples for analysis to measure 25-hydroxyvitamin D and lipid profile levels including non-high-density lipoprotein cholesterol and total cholesterol to high-density lipoprotein cholesterol ratio. Results: The current study demonstrated that coffee consumption rate and vitamin D deficiency were significantly positively connected with the total cholesterol to high-density lipoprotein cholesterol ratio ( p  = .003) in women with vitamin D deficiency. In addition, vitamin D deficiency alone correlated positively with non-high-density lipoprotein cholesterol levels and the total cholesterol to high-density lipoprotein cholesterol ratio ( p  = .010) and ( p  = .002), respectively. Conclusion: Higher coffee consumption rate among women with vitamin D deficiency significantly elevated total cholesterol to high-density lipoprotein cholesterol ratio that may increase woman’s risk of hyperlipidemia.